2011
DOI: 10.3109/09638288.2011.638031
|View full text |Cite
|
Sign up to set email alerts
|

Early maladaptive schema factors, pain intensity, depressiveness and pain disability: an analysis of biopsychosocial models of pain

Abstract: The study supported the importance of early emotional adversities in predicting depressiveness especially among pain patients. Depressiveness was the main predictor of pain disability in the pain patient group and as the pain duration increased, the significance of pain intensity on disability vanished. Pain intensity was the main predictor of pain disability in the control group.\

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 78 publications
0
14
0
1
Order By: Relevance
“…In this study we replicated the results of numerous earlier studies on the role of depression as a co‐occurent factor in chronic pain, alexithymia and EMSs. In earlier studies depression occurred as a mediator between pain disability and alexithymia (Saariaho, Saariaho, Mattila, Karukivi & Joukamaa, ) and between second‐order EMSs factors and pain disability (Saariaho et al ., ). Our exploration of scores on EMSs in different states of depression in alexithymic and nonalexithymic patients showed that higher EMSs scores are related to the severity of depression and also to alexithymia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study we replicated the results of numerous earlier studies on the role of depression as a co‐occurent factor in chronic pain, alexithymia and EMSs. In earlier studies depression occurred as a mediator between pain disability and alexithymia (Saariaho, Saariaho, Mattila, Karukivi & Joukamaa, ) and between second‐order EMSs factors and pain disability (Saariaho et al ., ). Our exploration of scores on EMSs in different states of depression in alexithymic and nonalexithymic patients showed that higher EMSs scores are related to the severity of depression and also to alexithymia.…”
Section: Discussionmentioning
confidence: 97%
“…EMSs have been found in various disorders, such as depression (Renner, Lobbestael, Peeters, Arntz & Huibers, 2012), eating disorders (Anderson, Rieger & Caterson, 2006;Unoka, T€ olgyes, Czobor & Simon, 2010), personality disorders (Carr & Francis, 2010), posttraumatic stress disorder (Cockram, Drummond & Lee, 2010), and substance abuse (Shorey, Stuart & Anderson, 2013). In a study comparing chronic pain patients with a control sample the results showed that chronic pain patients had more EMSs than the control group (Saariaho, Saariaho, Karila & Joukamaa, 2011) and in an another study the second-order factor structure of EMSs in chronic pain patients was different from that of the control sample (Saariaho, Saariaho, Karila & Joukamaa, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Self-sacrificing tendencies were found to moderate the relationship between pain and the physical symptoms in rheumatoid arthritis, 55 , 56 which is associated with depression. 57 Another study supporting a pathway from depression to pain was conducted by Saariaho et al 58 They revealed that the group of maladaptive schemas called “endangered” role (eg, disconnection rejection) showed pathways to depression, and from depression to pain disability in the pain patients, while the other group of maladaptive schemas, defined as the “encumbered” role (eg, self-sacrificing), exhibited a direct pathway to pain disability.…”
Section: Introductionmentioning
confidence: 99%
“…Pain is a symptom associated with significant impairments to an individual's quality of life and functioning, affecting mobility, work activities, social interaction, getting along, and self‐care . When present during the gestational period, pain is also associated with disability, since it affects the ability of pregnant women to work, sleep, and conduct daily activities .…”
Section: Discussionmentioning
confidence: 99%